Study of the Biochemical Role of Vitamin C (Ascorbic Acid) in the Animal Body - Stanikzai, Nasrin (Journal of Natural Sciences – Kabul University, 2025)
Vitamin C, also known as ascorbic acid and L-ascorbic acid, is a vitamin found in various foods and sold as a dietary supplement. Vitamins are essential nutrients that play important roles in various biochemical activities. A deficiency in vitamins can lead to metabolic disorders. Vitamin C functions as an antioxidant that protects the skin from the damaging effects of sunlight, improves iron absorption in the body, and helps protect cells from oxidative stress during a stroke. Vitamin C has also been used as a food preservative for pets and has been proven to act as an antioxidant in pond turtles. The biochemical role of vitamin C in the animal body includes collagen biosynthesis, carnitine biosynthesis, dopamine hydroxylation, as well as the hydroxylation of steroids, aromatic drugs, and carcinogens in liver microsomes.